Anticardiolipin antibody, recurrent thrombosis, and warfarin withdrawal. Issue 12 (December 1985) - Asherson, R A; Chan, J K; Harris, E N; Gharavi, A E; Hughes, G R
Abstract : Antibodies to cardiolipin, closely related to the 'lupus anticoagulant', are strongly implicated in the pathogenesis of thrombosis. We record six patients, all with high titres of these antibodies (greater than SD) in serum, who developed recurrent vascular occlusions six to 12 weeks after warfarin withdrawal. Five of the six had deep vein thrombosis, while the sixth suffered a myocardial infarction. To minimise the risk of 'recurrent' thrombosis it is strongly suggested that such patients remain on long-term anticoagulation, pending the reduction of high antibody levels.